Design And Simulation Of High Linearity And Stability Operational Amplifier Circuitry For Amperometric Sensor - Shin Shin, Angie Lee (2017)

(untitled)
Redox sensor is widely used to detect certain analytes of a chemical solution especially concentration of a chemical solution. Redox sensor has advantages of detection of multiple ions inside a sensing areas by measurement and represent it in electrical current or voltage. However, sensitivity and output signal of sensor decreases due to miniaturization of sensing area. This thesis presents a design of a potentiostat that is able to process the redox sensor small output signal in the range of 0 A to 10 μA and has a linear and amplified voltage signal for integration with analogue digital conversion (ADC) circuit. It provides a stable output when the voltage supply,